Financial constraints and investment thirst in Chinese reverse merger companies. (25th March 2018) - Cheng, Zijian; Fleming, Grant; Liu, Zhangxin (Frank)
Abstract: Using a hand‐collected data set of Chinese reverse mergers (RM) between 2006 and 2015, we find that financial constraints are more serious and investment thirst higher for RM companies as compared with initial public offering (IPO) companies. For state‐owned enterprises (SOEs), listing via a RM or an IPO does not impact the level of financial constraints post‐listing, while SOE RMs have higher investment thirst than SOE IPOs. By contrast, non‐SOE RMs are under more financial constraints and have higher investment thirst than non‐SOE IPOs. These differences are not presented during the 4 Trillion Yuan stimulus period between 2008 and 2010.